Evidence-Based Complementary, Alternative and Integrated Medicine and Efficacy and Safety: Lung Cancer - Al-Worafi, Yaser Mohammed; Halboup, Abdulsalam; Kalluvalappil, Nabeel Ayappali; Alsergi, Wafa Mohammed (Taylor & Francis, 2025)
Complementary and Alternative Medicine (CAM) offers various non-conventional therapeutic approaches that are increasingly adopted by patients with lung cancer to alleviate symptoms, improve quality of life, and complement standard treatments. CAM interventions include herbal therapies, nutraceuticals, mindbody practices, acupuncture, massage, and energy-based therapies. These therapies provide symptom relief, such as reducing pain, nausea, fatigue, and anxiety, while also promoting immune modulation and psychological well-being. Despite promising anecdotal and clinical evidence, the integration of CAM into lung cancer care presents challenges, including inconsistent efficacy data, safety concerns, and potential interactions with conventional therapies. Healthcare professionals play a vital role in guiding patients by offering evidence-based advice on the safe use of CAM and supporting informed decision-making. Further research is essential to explore the mechanisms, efficacy, and long-term outcomes of CAM in lung cancer prevention and treatment. This chapter emphasizes the need for collaboration between CAM practitioners and oncologists to develop integrative oncology programs that provide holistic patient care.